The Hegemony of Global Capitalism in the Regulation of Electricity: The Electricity Policies of the Selected Southeast Asian Nations - Paryono, Paryono; Dimyati, Khudzaifah; Absori, Absori; Rismawati, Shinta Dewi (International Journal of Energy Economics and Policy, 2019)
This paper examines the effect of global capitalism on electricity policies in Southeast Asian countries: Singapore, the Philippines, Thailand, Malaysia and Indonesia. The purpose of this study is to get a picture of the electricity policy in a country. This research method compares the electricity regulation between countries in Southeast Asia. The results of this study are: the influence of global capitalism in electricity liberalization resulting in major changes in electricity power regulation in most Southeast Asian countries. Electricity infrastructure is mostly owned by the electricity capitalism of global capitalism. Which then makes the connection of the electrical energy system between countries for the sake of the electricity energy business. The hegemony of global capitalism plays a role through the liberalization and deregulation of electricity in Southeast Asian countries, the regulation of electricity in the Southeast Asia region is under absolute control by the power of capitalism of electricity. Keywords: Global Capitalism, Southeast Asian Countries, Electricity JEL Classifications: Q43, P12 DOI: https://doi.org/10.32479/ijeep.7360